Myxomycete colonization on translocated and non-translocated dead leaves from temperate and tropical forests - Rojas Alvarado, Carlos Alonso (2020)
Samples of dead leaves on the forest floor were collected from a locality in central Costa Rica and another locality in northwest Arkansas in the United States and then were placed in fine-mesh nylon bags, autoclaved and left out in the field for four months. Half of the bags prepared with sterile material from each country were placed out in the country where they were collected, and the other half were placed in the other country. A characterization of forest structure and ground leaf chemistry was carried out for both localities and both leaf types. When recollected, all samples were processed for myxomycetes with the use of the moist chamber culture technique. The cultures yielded a total of 156 records of myxomycetes representing 16 species, but only 13 records and six species were isolated from the samples left out in Costa Rica. One hundred percent of cultures placed out in Arkansas produced myxomycetes, whereas only 68% of those placed out in Costa Rica were positive for these organisms. Differences in species richness and number of records were observed across forests where the samples were placed out, and no differences were observed based on the origin of the leaves. Results suggested that myxomycete colonization in the studied areas is primarily affected by the dynamics of the forest type and secondarily by substrate attributes. Some myxomycete species recorded on leaves with poorer chemical values are also consistent with field data. In the present study, the more open character of the temperate forest in Arkansas without a film of water layer covering the leaves on the ground seemed to have played a role in the establishment of myxomycete propagules in the sterile material during the time of the investigation.